The roles of miRNAs in human breast cancer and canine mammary tumor - Yu, Richard Ming Chuan; Cheah, Yoke Kqueen (BioMed Central, 2017)
MicroRNAs have become a hot topic in cancer research nowadays due to their important role not only on cancer development, progression, invasion but also on repression of cancer related genes. With advanced technologies, these microRNAs can easily be detected from biopsy samples and blood for early diagnosis, prognosis and treatment. Due to increasing demand of research in exploring expression profile of microRNAs with respect to different subtypes of breast cancer, this review aimed to provide an update on microRNA database available resources, canine breast cancer models, the role of microRNA as oncomir or oncosupressor, detection of microRNAs and potential of miRNAs for breast cancer treatment.